2013
DOI: 10.1038/nchem.1567
|View full text |Cite
|
Sign up to set email alerts
|

Phase-transfer-catalysed asymmetric synthesis of tetrasubstituted allenes

Abstract: Allenes are molecules based on three carbons connected by two cumulated carbon-carbon double bonds. Given their axially chiral nature and unique reactivity, substituted allenes have a variety of applications in organic chemistry as key synthetic intermediates and directly as part of biologically active compounds. Although the demands for these motivated many endeavours to make axially chiral, substituted allenes by exercising asymmetric catalysis, the catalytic asymmetric synthesis of fully substituted ones (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(94 citation statements)
references
References 26 publications
1
93
0
Order By: Relevance
“…Therefore, there have been so far many reports on the asymmetric synthesis of optically active allenes [27,28]. Among them, we focused on the base-catalyzed isomerization of alkynylesters into allenoesters from the atom-economical perspective [8,9,[29][30][31]. …”
Section: Isomerization Of Alkynoates To Allenoatesmentioning
confidence: 99%
“…Therefore, there have been so far many reports on the asymmetric synthesis of optically active allenes [27,28]. Among them, we focused on the base-catalyzed isomerization of alkynylesters into allenoesters from the atom-economical perspective [8,9,[29][30][31]. …”
Section: Isomerization Of Alkynoates To Allenoatesmentioning
confidence: 99%
“…[17] 2) Central-to-axial chirality transfer can also be achieved by the kinetic resolution of racemic compounds [18] or enzymatic desymmetrization of prochiral allenic diols. [19] 3) Direct asymmetrics ynthesis can proceed by the introduction of stoichiometricc hiral reagents, [20] transition metal catalysis with Pd [21a-i] or Cu, [21j] or organic compound-directed catalysis, [5,22] in which the dynamic kinetic asymmetrict ransformation (DYKAT) protocol has been applied. [21d] Of these strategies for the asymmetric synthesis of allenes, the DYKATstrategy [23] attracted our attention because the DYKATa nd related dynamic kinetic resolution [24] strategies have provent ob eapowerful in asymmetric synthesis as they can efficiently transform racemic starting materials into as ingle stereoisomeric product.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, to date,a symmetric catalytic methods to access tetrasubstituted chiral allenes have rarely been exploited. [10] Cooperative Cu/Pd catalysis is an efficient strategy for the enantioselective carbonboration of alkenes. [11,12] We envisioned that ab imetal catalytic system might enable the allenylcopper intermediate to be efficiently trapped by aC electrophile with high stereoselectivity.A saresult, nonracemic,m ultisubstituted allenes could be prepared.…”
mentioning
confidence: 99%
“…Replacement of CuCl with CuBr can slightly increase the er value (entry 7). Chiral ligand screening showed that the SOPs L1-L4 were the preferred ligands in terms of enantioselectivity,whereas poor er values were achieved when employing commercially available chiral ligands (L5-L8;e ntries [8][9][10][11][12][13][14]. Theu se of 10 mol %t ri(2-furyl)phosphine (TFP) as an additive and replacing NaOMe with NaOEt could further improve the er value slightly (entries 15 and 16).…”
mentioning
confidence: 99%